5(2x+4)=3(5x+3)+6

Simple and best practice solution for 5(2x+4)=3(5x+3)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x+4)=3(5x+3)+6 equation:


Simplifying
5(2x + 4) = 3(5x + 3) + 6

Reorder the terms:
5(4 + 2x) = 3(5x + 3) + 6
(4 * 5 + 2x * 5) = 3(5x + 3) + 6
(20 + 10x) = 3(5x + 3) + 6

Reorder the terms:
20 + 10x = 3(3 + 5x) + 6
20 + 10x = (3 * 3 + 5x * 3) + 6
20 + 10x = (9 + 15x) + 6

Reorder the terms:
20 + 10x = 9 + 6 + 15x

Combine like terms: 9 + 6 = 15
20 + 10x = 15 + 15x

Solving
20 + 10x = 15 + 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
20 + 10x + -15x = 15 + 15x + -15x

Combine like terms: 10x + -15x = -5x
20 + -5x = 15 + 15x + -15x

Combine like terms: 15x + -15x = 0
20 + -5x = 15 + 0
20 + -5x = 15

Add '-20' to each side of the equation.
20 + -20 + -5x = 15 + -20

Combine like terms: 20 + -20 = 0
0 + -5x = 15 + -20
-5x = 15 + -20

Combine like terms: 15 + -20 = -5
-5x = -5

Divide each side by '-5'.
x = 1

Simplifying
x = 1

See similar equations:

| 4/7-19/28 | | 2x^4(x^3)=0 | | e^1-8x=9 | | 2m*3n=36 | | 6/16=4/c | | 14a+19b+4c+2c-2b-4a= | | Y/6-y=5 | | 2x(x^3)=0 | | u/4-2=-18 | | 2m*3m=36 | | 3(2m+1)=27 | | cos48=x/11 | | -28=2+5v | | xy=-2qx-x^3+2r | | 2(x^3)=0 | | -4=8+u | | 1/4x^2-29/16x-3/2=0 | | 14x-(4x+12)-11x-(3-4x)=0 | | 17=8+3v | | 22y-y^2=72 | | 2x+2y+2+4= | | 5y+17=112 | | 3(x-3)+5=3x-4 | | 15x^4+6x^3-113=0 | | 4x-100=-50 | | y=12x^2-11x-15 | | -6x-1=-11-7x | | (x-i)*(x-i)+(x+i)*(x+i)=0 | | 0=9(k*6)+33 | | 0.8x+5=6-0.2x | | 3x+5y=33x | | X+4-3x=2-x |

Equations solver categories